New species, new records, and distribution of Campodeidae (Diplura) in Anatolia - Sendra, Alberto; Teruel, Santiago; Satar, Ali; Tusun, Sadreddin; Özbay, Cengizhan (Zootaxa, 2010)
The campodeid dipluran fauna from Anatolia was studied from samples collected from the Black Sea, southeastern, Aegean, and eastern regions of Turkey. A total of 16 species were collected: Campodea s. str. (10 species), Dicampa (2), Eutrichocampa (2), Libanocampa (1), and Edriocampa (1). Two new species are described: Campodea (Campodea) anae Sendra & Teruel n. sp. from northern Anatolia and Campodea (Campodea) sarae Sendra & Teruel n. sp. from Denizli, in southeastern Turkey. These results suggest that additional sampling is needed in other parts of Turkey to adequately characterize the campodeid fauna. The known campodeid biodiversity of Anatolia stands at 23 species, 3 times less than the Iberian peninsula.